Śladem promieni Czarnego słońca Kurahary Koreyoshiego. Negrofilia w kinie japońskim - Bochniarz, Marek; Sztafiej, Przemysław (Przestrzenie Teorii, 2018)
This article explores two films by Kurahara Koreyoshi: Black Sun and Safari 5000, in the context of the scholars John Russell and Jonathan D. Mackintosh’s approaches to racism and so-called negrophilia in Japanese mass-culture and cinema. The authors argue that cultural stereotypes even have a negative impact on the artistically original Japanese directors, who only seem to be independent and express their thoughts freely.